Bromeliads going batty: pollinator partitioning among sympatric chiropterophilous Bromeliaceae - Aguilar-Rodríguez, Pedro Adrián; Tschapka, Marco; García-Franco, José G; Krömer, Thorsten; MacSwiney G, M Cristina (AoB plants, 2019)
Pre-pollination mechanisms for isolation among sympatric bat-pollinated plants are largely unknown. We investigated the mechanisms for reproductive segregation between four sympatric chiropterophilous bromeliads in Veracruz, Mexico. With ex situ and in situ manual pollination treatments we determined the breeding system by assessing fruiting and seedling success and sampled bat visitors using mist-nets and infrared cameras. Bromeliads showed staggered flowering, different pollen deposition sites on the body of the pollinator and differences in the reward offered. These traits may have evolved to reduce the competitive costs of sharing pollinators while providing a constant supply of food for the nectarivorous bat community. Abstract Pollinators can be a limited resource and natural selection should favour differences in phenotypic characteristics to reduce competition among plants. Bats are important pollinators of many Neotropical plants, including the Bromeliaceae; however, the pre-pollination mechanisms for isolation among sympatric bat-pollinated bromeliads are unknown. Here, we studied the mechanisms for reproductive segregation between Pitcairnia recurvata, Pseudalcantarea viridiflora, Werauhia noctiflorens and W. nutans. The study was conducted at Los Tuxtlas Biosphere Reserve, in Veracruz, Mexico We carried out ex situ and in situ manual pollination treatments to determine the breeding system by assessing fruiting and seedling success and sampled bat visitors using mist-nets and infrared cameras. We determined the nocturnal nectar production pattern, estimating the energetic content of this reward. All four bromeliads are self-compatible, but only P. recurvata appears to require pollinators, because the physical separation between anthers and stigma prevents self-pollination, it is xenogamous and presents a strictly nocturnal anthesis. The bats Anoura geoffroyi, Glossophaga soricina and Hylonycteris underwoodi are probable pollinators of three of the studied bromeliads. We did not record any animal visiting the fourth species. The flowering season of each species is staggered throughout the year, with minimal overlap, and the floral morphology segregates the locations on the body of the bat where the pollen is deposited. The most abundant nectar per flower is provided by P. viridiflora, but P. recurvata offers the best reward per hectare, considering the density of flowering plants. Staggered flowering, different pollen deposition sites on the body of the pollinator and differences in the reward offered may have evolved to reduce the competitive costs of sharing pollinators while providing a constant supply of food to maintain a stable nectarivorous bat community.